2009
DOI: 10.1212/wnl.0b013e3181ae7af1
|View full text |Cite
|
Sign up to set email alerts
|

Course in Parkinson disease subtypes

Abstract: The three subtypes of Parkinson disease have different courses which are concordant with the differences in brain biochemical abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
218
4
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(237 citation statements)
references
References 38 publications
11
218
4
4
Order By: Relevance
“…In addition, differences were observed among ART, TDT and MT groups in terms of the WHOQOL-OLD domain 4 scores. Although previous studies have demonstrated that these PD subtypes have different courses, 41,42 ours is the first to show that the level of social participation differs among them.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition, differences were observed among ART, TDT and MT groups in terms of the WHOQOL-OLD domain 4 scores. Although previous studies have demonstrated that these PD subtypes have different courses, 41,42 ours is the first to show that the level of social participation differs among them.…”
Section: Discussionmentioning
confidence: 56%
“…4,8,17,42 Therefore, various manifestations can have a negative effect on quality of life. 13,37,38 This underscores the notion that non-motor symptoms should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline MDS‐UPDRS and putamen DAT SBR demonstrated a modest correlation, as in other clinical studies. The lack of correlation may reflect the heterogeneity of presentation, course, and response to therapy, a hallmark of PD 53, 54, 55. The PPMI longitudinal data will examine whether baseline biomarkers and/or short‐term change in baseline biomarkers are predictive of longitudinal PD progression outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It was also noted that severity of tremor does not correlate with severity of dopamine loss or clinical disease progression (Zaidel et al, 2009). Rajput et al (2009) reported that tremor-dominant PD patients showed slower disease progression and less dementia than did akinesia/rigidity-dominant PD patients. A postmortem histopathological study showed that dopaminergic cells in the midbrain retrorubral area, which project to the dorsolateral striatum and ventromedial thalamus, are more severely affected in tremor-dominant PD patients than in akinesia/rigidity-dominant PD patients (Paulus & Jellinger, 1991).…”
Section: Clinicopathological Studiesmentioning
confidence: 99%
“…A recent PET study suggests that the metabolic pattern of tremor-dominant PD is significantly different from that of akinesia/rigidity-dominant PD (Mure et al, 2011). Patients with tremor-dominant PD exhibit better clinical prognoses and slower disease progression with less cognitive decline (Louis et al, 1999;Marras et al, 2002;Rajput et al, 2009). Using FDG-PET, Mure et al (2011) indicated that these clinical findings correlate with a slow deterioration of the metabolic pattern in patients with tremor-dominant PD.…”
Section: Positron Emission Tomography (Pet) and Single Photon Emissiomentioning
confidence: 99%